(untitled) (Security Dialogues, 2023)
The goal of this paper is a comparative analysis of the current and upcoming challenges facing Serbia and North Macedonia in the economic, security, and political context. The research question is following: whether small states, such as Serbia and NorthMacedonia, can overcome instability in international relations and the region, while at thesame time preserving the achieved levels of economic development, security environment and internal political stability. Through a comparative analysis of these two countries, we will present the risks, challenges and threats faced by these two small countries in the current year, as well as what unites and what separates these countries in the context of newly emerging international circumstances. Also, we will analyse the real potentials of regional cooperation in the Western Balkans from the point of view of the interstate cooperation of these two countries, as a potential determinant of creating sustainability and stability in the economic, political and security domains.